1974
DOI: 10.1111/j.1365-2125.1974.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Rx 72601, a New Anticholinesterase in Man: Reversal of Competitive Neuromuscular Blockade

Abstract: The effect of RX 72601, neostigmine plus atropine, or saline on neuromuscular blockade with (+)-tubocurarine was studied in a double blind trial in four healthy male volunteers. 2 The methods used to assess neuromuscular function were voluntary grip strength and indirectly evoked muscle twitches. The muscarinic action was assessed by measuring intestinal motility with a pressure sensitive radio pill, and auscultation of the abdomen. Blood pressure and pulse rate were also recorded. The degree of acetylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1975
1975
1975
1975

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…In addition, results from earlier work in both animals (Metcalf & Dettmar, 1975;G. Metcalf, G. Shilcock & M.H. Smith, unpublished observations) and man (Dettmar et al, 1974b) when applied to the present experiments suggest that the doses used would cause virtually complete inhibition of acetylcholinesterase in the restricted areas of drug application. Alternatively, most of the previous studies have used carbachol as the cholinomimetic agent; this drug is known to stimulate both muscarinic and nicotinic receptors in the periphery, and Myers (1974) has suggested that behavioural responses produced by this drug may result from stimulation of CNS receptors with muscarinic characteristics.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In addition, results from earlier work in both animals (Metcalf & Dettmar, 1975;G. Metcalf, G. Shilcock & M.H. Smith, unpublished observations) and man (Dettmar et al, 1974b) when applied to the present experiments suggest that the doses used would cause virtually complete inhibition of acetylcholinesterase in the restricted areas of drug application. Alternatively, most of the previous studies have used carbachol as the cholinomimetic agent; this drug is known to stimulate both muscarinic and nicotinic receptors in the periphery, and Myers (1974) has suggested that behavioural responses produced by this drug may result from stimulation of CNS receptors with muscarinic characteristics.…”
Section: Discussionsupporting
confidence: 57%
“…A higher dose of RX7260 1 produced mydriasis and nystagmus. This duration of action corresponds to the duration of acetylcholinesterase inhibition previously measured in vivo (Dettmar et al, 1974b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar biochemical result was obtained in man, suggesting that this same dose would be effective in reversing the effects of non-depolarizing muscle relaxants in a clinical situation. This suggestion has now been confirmed in volunteer studies where it was found that 10 /*g/kg RX 72601 was effective in reversing partial neuromuscular block-ade induced by tubocurarine (Dettmar, Gillett et al, 1974).…”
Section: Discussionmentioning
confidence: 76%
“…Doses necessary to exert these so-called anti-curare effects had only minimal effects on the cardiovascular and respiratory systems, so that there was no need to pretreat animals with atropine before the administration of RX 72601. These favourable animal results have since been extended in human volunteer studies (Dettmar, Gillett et al, 1974) where the standard combination of neostigmine plus atropine was compared with RX 72601 given alone for both its anticurare properties and the incidence of cholinergic stimulation at muscarinic sites. The results obtained confirmed the ability of RX 72601 to reverse neuromuscular blockade produced by nondepolarizing relaxants and the lack of side effects produced by the drug.…”
Section: Discussionmentioning
confidence: 96%